2013
DOI: 10.1002/nur.21545
|View full text |Cite
|
Sign up to set email alerts
|

Sleep loss and its effects on health of family caregivers of individuals with primary malignant brain tumors

Abstract: Sleep loss places caregivers at risk for poor health. Understanding correlates of sleep loss and relationships to health may enable improvement of health of caregivers of individuals with primary malignant brain tumors (PMBT). In this cross-sectional, descriptive study of 133 caregivers, relationships were examined between sleep loss and physical, mental, emotional, and social health at time of patient diagnosis. Sleep loss was not related to physical health. Shorter total sleep time was associated with greate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 67 publications
1
38
0
2
Order By: Relevance
“…These factors appeared to be interrelated. Previous studies have shown that fatigue can have deleterious effects on the immune system by placing people at cardiovascular risk and altering the management of their emotions [ 40 , 41 ]. Family support has been documented in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…These factors appeared to be interrelated. Previous studies have shown that fatigue can have deleterious effects on the immune system by placing people at cardiovascular risk and altering the management of their emotions [ 40 , 41 ]. Family support has been documented in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, another study found that the quantity of care provided (e.g., hours spent providing care and frequency of providing different types of care) was not significantly related to overall SWB among cancer caregivers . Perceptions of greater social support, however, have been correlated with better overall SWB among cancer caregivers . Theory suggests that low levels of social support may negatively impact caregivers' SWB, as caregivers have fewer opportunities to engage in meaning‐making with important others .…”
Section: Introductionmentioning
confidence: 94%
“…Although the cancer caregiving literature on SWB is limited [16,18,[20][21][22], a number of studies have examined relationships between specific aspects of SWB and mental health in cancer patients [23]. These studies have found that higher levels of meaning and peace are consistently related to better mental health outcomes [13,16,24,25].…”
Section: Spiritual Well-being Of Family Caregiversmentioning
confidence: 99%
“…However, there are inconsistencies in the operational definitions or tools used in nursing studies. In addition, more than one instrument is mainly used in the same nursing study to measure health (Doumit, Nasser, & Hanna, ; Pawl, Lee, Clark, & Sherwood, ). Examples of applications and instruments used in nursing research are included in Table .…”
Section: Resultsmentioning
confidence: 99%